Potential Identification of Community-Based Tourism Product Development in Santong Tourism Village, North Lombok Regency, Indonesia - Oktomi Harja; Ruwaida Fajria Santi; Rizda Endean Ngoluanta Batubara; Jumraidin Jumraidin; Ainul Yakin; Putu Ari Nugraha; firman koma febdilan; Muh Ilham H; Ida Ayu Yadnya Sari Dewi Utami Pidada; Siti Lathifah (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: This community service activity is carried out with the main objective of identifying the potential for developing tourism products in Santong Tourism Village which originates from the economic, social and cultural potential of the community in the context of developing quality and competitive tourism products in Santong Tourism Village. Method: The community service employs (1) field survey to identify current conditions and the need for intervention in the development of tourist village with data collection techniques ranging from direct observation, in-depth interview, to documentation, and (2) workshop which includes short lectures, guided group discussions, demonstrations, and simulations. The data obtained are all primary data obtained directly from Pokdarwis, other tourism actors, as well as Santong’s local community. Result: The 2 (two) main outputs of this community service activity are (1) tour package and culinary product prototypes that integrate various natural potentials and local community wisdom, as well as (2) needs identification for homestay development in Santong Tourism Village. Contribution: Providing new insights and skills to the local community in developing integrated and quality tourism products that can provide broader economic impact the people of Santong Tourism Village.